PENTINGNYA POLA ASUH ORANG TUA TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK - Marzuki Marzuki; Lukis Alam; Loso Judijanto; Jepri Utomo; Farhan Ferian (CV. ADIBA AISHA AMIRA, 2025)
In the current era, emotional attitudes are important to face technological growth. The negative influence caused by the use of technology can damage children's social attitudes. The family environment, especially parents, is an aspect that has a big influence on children's social development. The family is the best forum for forming a child's personality, including social and emotional changes. The aim of this research is to determine the importance of parenting patterns carried out by parents and their impact on children's social and emotional development. By using literature review methodology, this research includes qualitative descriptive research.